Revisiting the Tissue Microenvironment of Infectious Mononucleosis: Identification of EBV Infection in T Cells and Deep Characterization of Immune Profiles - Barros, Mário Henrique M.; Vera-Lozada, Gabriela; Segges, Priscilla; Hassan, Rocio; Niedobitek, Gerald (Frontiers in Immunology, 2019)
To aid understanding of primary EBV infection, we have performed an in depth analysis of EBV-infected cells and of local immune cells in tonsils from infectious mononucleosis (IM) patients. We show that EBV is present in approximately 50% of B-cells showing heterogeneous patterns of latent viral gene expression probably reflecting different stages of infection. While the vast majority of EBV+ cells are B-cells, around 9% express T-cell antigens, with a predominance of CD8+ over CD4+ cells. PD-L1 was expressed by a median of 14% of EBV+ cells. The numbers of EBER+PD-L1+ cells were directly correlated with the numbers of EBER+CD3+ and EBER+CD8+ cells suggesting a possible role for PD-L1 in EBV infection of T-cells. The microenvironment of IM tonsils was characterized by a predominance of M1-polarized macrophages over M2-polarized cells. However, at the T-cell level, a heterogeneous picture emerged with numerous Th1/cytotoxic cells accompanied and sometimes outnumbered by Th2/regulatory T-cells. Further, we observed a direct correlation between the numbers of Th2-like cells and EBV– B-cells. Also, a prevalence of cytotoxic T-cells over Th2-like cells was associated with an increased viral load. These observations point to contribution of B- and Th2-like cells to the control of primary EBV infection. 35% of CD8+ cells were differentiated CD8+TBET+ cells, frequently detected in post-capillary venules. An inverse correlation was observed between the numbers of CD8+TBET+ cells and viral load suggesting a pivotal role for these cells in the control of primary EBV infection. Our results provide the basis for a better understanding of immune reactions in EBV-associated tumors.